Effects of tiotropium + olodaterol versus tiotropium or placebo by COPD disease severity and previous treatment history in the OTEMTO® studies. Issue 1 (December 2016) - Singh, Dave; Gaga, Mina; Schmidt, Olaf; Bjermer, Leif; Grönke, Lars; Voß, Florian; Ferguson, Gary
Abstract Background As lung function declines rapidly in the early stages of chronic obstructive pulmonary disease (COPD), the effects of bronchodilators in patients with moderate disease and those who have not previously received maintenance therapy are of interest. OTEMTO® 1 and 2 were two replicate, 12-week, Phase III studies investigating the benefit of tiotropium + olodaterol on lung function and quality of life in patients with moderate to severe disease.Post hoc analyses were performed to assess the benefits for patients according to disease severity and treatment history. Methods Four subgroup analyses were performed: Global initiative for chronic Obstructive Lung Disease (GOLD) 2/3, GOLD A/B/C/D, treatment naive/not treatment naive and receiving inhaled corticosteroids (ICS) at baseline/not receiving ICS at baseline. Primary end points were change in forced expiratory volume in 1 s (FEV1 ) area under the curve from 0 to 3 h response, change in trough FEV1 and St George's Respiratory Questionnaire (SGRQ) total score. Transition Dyspnoea Index (TDI) focal score was a secondary end point, and SGRQ and TDI responder analyses were further end points; all were assessed at 12 weeks. Results In all subgroups, patients receiving tiotropium + olodaterol responded better overall than those receiving tiotropium monotherapy. Improvements with tiotropium + olodaterol over placebo or tiotropium monotherapy were noted across GOLD 2/3 and GOLD A/B/C/D; however, improvements in SGRQ total score were most evident in the GOLD B subgroup. Moreover, lung-function outcomes were generally greater in those patients who had been receiving previous long-acting bronchodilator and/or ICS maintenance treatment. Conclusions These data suggest that tiotropium + olodaterol should be considered as a treatment option in patients with moderate COPD who are initiating maintenance therapy, as well as those with more severe disease. Trial registration ClinicalTrials.gov:NCT01964352 andNCT02006732 .